Pengaruh Lingkungan Kerja, Budaya Organisasi, Kompensasi, dan Beban Kerja Terhadap Produktivitas Pegawai: Studi Pada SKPD Kota Tasikmalaya - Annisa Nur Hidayah Sitorus; Dedi Kusmayadi; Apip Supriadi (ProBisnis : Jurnal Manajemen, 2026)
The productivity of government employees is influenced by various internal organizational factors that must be effectively managed to enhance overall public sector performance. This study aims to analyze the effects of work environment, organizational culture, compensation, and workload on employee productivity within the Regional Work Units (SKPD) of Tasikmalaya City. A quantitative approach was employed using a survey method involving 250 employees selected through proportioned stratified random sampling. Data were analyzed using path analysis. The findings indicate that the work environment, organizational culture, compensation, workload, and employee productivity are all categorized as very good. Partially, each of the four independent variables shows a positive and significant effect on employee productivity. Simultaneously, the work environment, organizational culture, compensation, and workload also exert a positive and significant influence on productivity. These results highlight the importance of strengthening a conducive work environment, developing a positive organizational culture, particularly through the internalization of the BerAKHLAK values, which enhancing performance-based compensation systems, and improving workload management to boost employee productivity within the SKPD of Tasikmalaya City.